Mapping Craft Industry Cluster Development In Madura To Enhance Local Economic Competitiveness - Firstiani, Rizka (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
The purpose of this study is to identify the potential of the creative economy in the craft industry subsector in Madura that can be developed as an economic potential through cluster grouping with K-Means Clustering analysis technique. The results of this study indicate that the craft industry in Madura has not fully entered into a dynamic cluster. The problems that result in some craft industries in Madura that have not entered into dynamic clusters are due to weak spatial identity, weak specialist supplier networks, lack of economic specialization, still not optimal labor specialization, still using simple production technology and unable to innovate products, and not having a network of business partners resulting in minimal development of market information obtained.